Treatment for Brain Metastases: ASCO-SNO-ASTRO Guideline. Issue 5 (10th February 2022) - Vogelbaum, Michael A.; Brown, Paul D.; Messersmith, Hans; Brastianos, Priscilla K.; Burri, Stuart; Cahill, Dan; Dunn, Ian F.; Gaspar, Laurie E.; Gatson, Na Tosha N.; Gondi, Vinai; Jordan, Justin T.; Lassman, Andrew B.; et al.
Abstract : PURPOSE: To provide guidance to clinicians regarding therapy for patients with brain metastases from solid tumors. METHODS: ASCO convened an Expert Panel and conducted a systematic review of the literature. RESULTS: Thirty-two randomized trials published in 2008 or later met eligibility criteria and form the primary evidentiary base. RECOMMENDATIONS: Surgery is a reasonable option for patients with brain metastases. Patients with large tumors with mass effect are more likely to benefit than those with multiple brain metastases and/or uncontrolled systemic disease. Patients with symptomatic brain metastases should receive local therapy regardless of the systemic therapy used. For patients with asymptomatic brain metastases, local therapy should not be deferred unless deferral is specifically recommended in this guideline. The decision to defer local therapy should be based on a multidisciplinary discussion of the potential benefits and harms that the patient may experience. Several regimens were recommended for non–small-cell lung cancer, breast cancer, and melanoma. For patients with asymptomatic brain metastases and no systemic therapy options, stereotactic radiosurgery (SRS) alone should be offered to patients with one to four unresected brain metastases, excluding small-cell lung carcinoma. SRS alone to the surgical cavity should be offered to patients with one to two resected brain metastases. SRS, whole brain radiation therapy, or their combination are reasonable options for other patients. Memantine and hippocampal avoidance should be offered to patients who receive whole brain radiation therapy and have no hippocampal lesions and 4 months or more expected survival. Patients with asymptomatic brain metastases with either Karnofsky Performance Status ≤ 50 or Karnofsky Performance Status < 70 with no systemic therapy options do not derive benefit from radiation therapy. Additional information is available at www.asco.org/neurooncology-guidelines .